Genotoxic Damage During Brain Development Presages Prototypical Neurodegenerative Disease - Kisby, Glen E.; Spencer, Peter S. (Frontiers in Neuroscience, 2021)
Western Pacific Amyotrophic Lateral Sclerosis and Parkinsonism-Dementia Complex (ALS/PDC) is a disappearing prototypical neurodegenerative disorder (tau-dominated polyproteinopathy) linked with prior exposure to phytogenotoxins in cycad seed used for medicine and/or food. The principal cycad genotoxin, methylazoxymethanol (MAM), forms reactive carbon-centered ions that alkylate nucleic acids in fetal rodent brain and, depending on the timing of systemic administration, induces persistent developmental abnormalities of the cortex, hippocampus, cerebellum and retina. The neurotoxic effects of MAM administered to rats during cortical brain development (specifically, gestation day 17) are used to model the histological, neurophysiological and behavioral deficits of human schizophrenia, a condition that may precede or follow clinical onset of motor neuron disease in subjects with sporadic ALS and ALS/PDC. Whle studies of migrants to and from communities impacted by ALS/PDC indicate the degenerative brain disorder may be acquired in juvenile and adult life, a proportion of indigenous cases shows neurodevelopmental aberrations in the cerebellum and retina consistent with MAM exposure in utero. MAM induces specific patterns of DNA damage and repair that associate with increased tau expression in primary rat neuronal culture and with brain transcriptional changes that parallel those associated with human ALS and Alzheimer disease. We examine MAM in relation to neurodevelopment, epigenetic modification, DNA damage/replicative stress, genomic instability, somatic mutation, cell-cycle reentry and cellular senescence. Since the majority of neurodegenerative disease lacks a genetic basis, research is needed to explore the hypothesis that early-life exposure to genotoxic agents may trigger or promote molecular events that culminate in neurodegeneration.